The Defect Monitoring of Micro Steel Fiber (MSF) Concrete Using Acoustic Emission Technique - Mat Jusoh, Mohamad Nor Zaini; Mohd Zuki, Sharifah Salwa; Ramasamy, Suchitra; Shahidan, Shahiron; Samsudin, Aizan; Abdul Manaf, Adib Fikri (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete is the important part of the structures. The strength and the performance of the concrete will be decreased during the age of the concrete due to effect of many factors. Concrete usually have its strength as planned but sometimes due to several factors, it suffers deteriorate in stage. Early identification of concrete deterioration is necessary. In the civil infrastructure, a lot of methods can be used to evaluate the damage of the concrete such as Acoustic Emission testing. This study is about effectiveness of micro steel fiber on concrete and monitoring the concrete conditions using Acoustic Emission technique. The concrete beam with size of 300 mm × 100 mm × 100 mm mix with specified percentage (0, 0.5, 0.75, 1.00,1.25) of micro steel fiber used as a sample for the Acoustic Emission test and determine the concrete strength. Acoustic Emission is a circumstances of a transient stress waves resulting from an immediate release of elastic energy, caused by mechanical deformity, initiation and generation of micro-cracks, dislocation movement, and at the irreversible change in material. Acoustic Emission signals contain useful information about the damage mechanisms that will know how effective the micro steel fiber on concrete. A major challenge of Acoustic Emission analysis is how to examine the Acoustic Emission information and signals due to the different damage mechanisms. Key words: deterioration, concrete monitoring, Acoustic Emission, concrete damages, damage mechanisms